2022
DOI: 10.3390/biology11030354
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Nanoparticles with Prodigiosin Rescue Hippocampal Damage Associated with Epileptic Seizures Induced by Pentylenetetrazole in Rats

Abstract: Background: Prodigiosin (PDG) is a red pigment synthesized by bacterial species with important pharmaceutical and biological activities. Here, we investigated the neuroprotective and anticonvulsant activities of green biosynthesized selenium formulations with PDG (SeNPs-PDG) versus pentylenetetrazole (PTZ)-induced epileptic seizures. Methods: Rats were assigned into six experimental groups: control; PTZ (60 mg/kg, epileptic model); sodium valproate (200 mg/kg) + PTZ; PDG (300 mg/kg) + PTZ; sodium selenite (0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…However, treatment with PG reduced the Cd-induced loss of neuronal cells as evidenced by a decrease in the production of pro-apoptotic proteins (Bax and caspase-3) and an increase in the expression of the anti-apoptotic protein Bcl-2. These findings are in agreement with those of Al Omairi, et al, (2022), who found that PG inhibited apoptosis in depressed rats. Lapenda et al (2020), recorded the anti-apoptotic action of PG and found that it inhibited the apoptotic cascade linked to stomach lesions brought on by injections of acidified ethanol by upregulating Bcl-2 and downregulating Bax and caspase-3.…”
Section: Discussionsupporting
confidence: 93%
“…However, treatment with PG reduced the Cd-induced loss of neuronal cells as evidenced by a decrease in the production of pro-apoptotic proteins (Bax and caspase-3) and an increase in the expression of the anti-apoptotic protein Bcl-2. These findings are in agreement with those of Al Omairi, et al, (2022), who found that PG inhibited apoptosis in depressed rats. Lapenda et al (2020), recorded the anti-apoptotic action of PG and found that it inhibited the apoptotic cascade linked to stomach lesions brought on by injections of acidified ethanol by upregulating Bcl-2 and downregulating Bax and caspase-3.…”
Section: Discussionsupporting
confidence: 93%
“…Since neurons are more sensitive to ROS injury during the early stages of brain development, an imbalance between ROS production and scavenging systems leads to neuronal damage. ROS-induced cytotoxicity is closely associated with and mostly precedes apoptotic cell death [ 9 , 43 ]. Interestingly, Gb and Ocs extracts protected hippocampal neurons and suppressed apoptosis associated with seizure propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is responsible for neuronal loss and death, which are directly related to epilepsy in in vitro animal models [ 9 , 10 ], and disturbs the antioxidant systems, including catalase (CAT), glutathione (GSH), superoxide dismutase (SOD), and lipid peroxidation (malondialdehyde [MDA]) systems [ 11 , 12 ]. Excess reactive oxygen species (ROS) activate pro-apoptotic signaling cascades, resulting in apoptotic cell death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism is not understood, the production of inflammatory cytokines in hepatic tissues as a consequence of aging may be linked to the activation of NF- κ B signaling pathway. NF- κ B is a key transcription factor of M1 macrophages and is required for the induction of a large number of inflammatory genes, including those encoding TNF- α and IL-6 [ 48 ]. Thus, blueberry may exhibit its anti-inflammatory effects by suppressing the activation of NF- κ B signaling as revealed by our results, although further studies are required to prove this.…”
Section: Discussionmentioning
confidence: 99%